Pros and cons of alternative policies aimed at promoting renewables - Dominique Finon (EIB Papers, 2007)
Following a brief review of the rationale for promoting renewable energy sources, this paper compares alternative policies to promote the production of renewable electricity. The focus is on feed-in tariffs (used in Germany, Spain, and France - for instance) and tradable green certificate (TGC) systems (United Kingdom and Italy, for instance). Considering economic theory and practical experience, the criteria for comparing these two alternatives are: cost-effectiveness, environmental effectiveness, and compatibility with market liberalisation. The paper argues that economic theory does not suggest a clear-cut advantage of one instrument over the other and it emphasises that, in any event, the choice of instrument depends on the relative importance attached to these criteria and on cultural factors such as faith - or lack thereof - in markets to help solve environmental problems. In this context, the paper questions the practical usefulness of a European-wide TGC system.
Keywords: 330; Förderung regenerativer Energien; EU-Staaten